PELAKSANAAN PERATURAN DAERAH KOTA PADANG NOMOR 8 TAHUN 2012 TENTANG, PENGAWASAN, PENGENDALIAN DAN PELARANGAN MINUMAN BERALKOHOL DI KECAMATAN PADANG UTARA - Meita Lefi Kurnia, Harry Sakti Adria dan (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Alcoholic beverages are beverages containing ethanol which are processed from agricultural products containing carbohydrates by fermentation. and distillation or fermentation without distillation, either by pre-treatment or not adding other ingredients or not, or processed by mixing concentrate with ethanol or by diluting beverages containing ethanol derived from fermentation. Liquor is synonymous with crime, therefore it is necessary to enact a regulation that regulates even to the point of prohibiting its circulation. The implementation of the Padang City Regional Regulation number 8 of 2012 concerning the supervision, control and prohibition of alcoholic beverages in the North Padang sub-district has been carried out in accordance with applicable regulations but has not been maximized. This is because there are still obstacles in the implementation of the regulation, in addition to the lack of human resources. In this case the Civil Service Police Unit which is inadequate and covers it to carry out its duties, there is not enough deterrent effect for sellers and collectors if caught controlling operations carried out by Civil service police Unit. Lack of legal awareness from the public in eliminating alcoholic beverages, due to the lack of socialization of related parties with the community directly.